HUBUNGAN PENGETAHUAN TENAGA KESEHATAN TENTANG KEWASPADAAN STANDAR PENGELOLAAN LIMBAH DENGAN KEPATUHAN PENGELOLAAN LIMBAH IBS RSUD WATES - Retnaning Tyas; Sri Hendarsih; Rosa Delima Ekwantini (Caring : Jurnal Keperawatan, 2018)
The operating room can be a major source of nosocomial infections caused by a variety of microorganisms, so the standard of infection prevention is very important in the operating room, given the contact with the patient's blood and body fluids, which increases the exposure of the patient to the perioperative worker.the low compliance of health personnel is due to the lack of knowledge, especially concerning standard precautions in waste management so that the purpose of this study is to prove the relationship between knowledge of healthcare Persons about standard precautions: waste management with compliance in waste management at the Central Surgery Installation. The type of research used is quantitative analytic observational (non experimental), with Fisher’s Exact research design, the sampling method used is total sampling. Samples taken as many as 37 health workers at the Central Surgery Installation of Wates Hospital consisting of anesthesia nurses, surgical nurses, anesthesiologists, and surgeons in April 2018. The research instrument used is questionnaire and observation sheet. After tabulated data with Fisher’s Exacttest with significance level of 0.05. The results showed that the knowledge of respondents with good category and For compliance. While the value of tabulation of good knowledge with good category compliance. Based on Fisher’s Exact test results obtained no correlation between knowledge of healthcare personsabout standard precautions: waste management with compliance in waste management with p-value significance value 0,554 (p> 0,05). There is no correlation between knowledge of healthcare persons about standard precautions: waste management with compliance in waste management at the Central Surgery Installation.